Does improved decision-making ability reduce the physiological demands of game-based activities in field sport athletes? - Gabbett, T. J.; Carius, J.; Mulvey, M. (The Journal of Strength and Conditioning Research, 2008)
This study investigated the effects of video-based perceptual training on pattern recognition and pattern prediction ability in elite field sport athletes and determined whether enhanced perceptual skills influenced the physiological demands of game-based activities. Sixteen elite women soccer players (mean +/- SD age, 18.3 +/- 2.8 years) were allocated to either a video-based perceptual training group (N = 8) or a control group (N = 8). The video-based perceptual training group watched video footage of international women's soccer matches. Twelve training sessions, each 15 minutes in duration, were conducted during a 4-week period. Players performed assessments of speed (5-, 10-, and 20-m sprint), repeated-sprint ability (6 x 20-m sprints, with active recovery on a 15-second cycle), estimated maximal aerobic power ([latin capital V with dot above]o2 max, multistage fitness test), and a game-specific video-based perceptual test of pattern recognition and pattern prediction before and after the 4 weeks of video-based perceptual training. The on-field assessments included time-motion analysis completed on all players during a standardized 45-minute small-sided training game, and assessments of passing, shooting, and dribbling decision-making ability. No significant changes were detected in speed, repeated-sprint ability, or estimated [latin capital V with dot above]o2 max during the training period. However, video-based perceptual training improved decision accuracy and reduced the number of recall errors, indicating improved game awareness and decision-making ability. Importantly, the improvements in pattern recognition and prediction ability transferred to on-field improvements in passing, shooting, and dribbling decision-making skills. No differences were detected between groups for the time spent standing, walking, jogging, striding, and sprinting during the small-sided training game. These findings demonstrate that video-based perceptual training can be used effectively to enhance the decision-making ability of field sport athletes; however, it has no effect on the physiological demands of game-based activities.